Students’ Perceptions Towards The Using Of Tiktok In Learning English At Sman 4 Poso - Bolendea, Sri Febriani; Macora, Yuliana Dg (Sintuwu Maroso Journal of English Teaching, 2024)
This study explores students' perceptions of using TikTok as a medium for learning English at SMAN 4 Poso. Employing a quantitative approach, data were collected through questionnaires and interviews from 64 students. The findings indicate that students have a positive perception of TikTok's use, with an average perception category reaching 77.10%. Students feel that TikTok provides engaging and easily accessible learning content, enhancing their motivation and English language skills. Although there are some challenges, such as the short duration of videos and the speed of explanations, TikTok is generally regarded as an effective tool to support English language learning.